Effect of Cowdung Compost Manure Rates of Application on the Growth and Leaf Yield of Spider Plant (Cleome gynandra L. Briq) in Jalingo, Taraba State, Nigeria - Y. A. Garjila; J. O. Shiyam; R. John (Archives of Current Research International, 2017)
Aim: The aim of the experiment was to evaluate the influence of different cowdung manure rates of application on growth and leaf yield performance of spider plant (Cleone gynandra L.). Study Design: The experiment was laid out in a randomized complete block design (RCBD) with four treatments including the control replicated five (5) times. Place and Duration of the Study: The field trial was conducted at the Teaching and Research Farm of Crop Science Department, Taraba State College of Agriculture Jallingo (Latitude 80° 50” N and longitude 11° 50” E) in 2014 and 2015 cropping seasons. Methodology: Treatments were four rates of cowdung manure application viz: 0, 3.0, 6.0 and 9.0 tones/ha incorporated into the soil one week prior to sowing. Random soil samples were taken with a soil auger at 0 - 30 cm depth and analyzed using standard laboratory procedures to determine the pre-planting and post-harvest soil nutrient contents and physical characteristics of the study area. Results: The results of soil analysis showed that the soil was acidic (pH(H2O) 5.9) with sandy loam texture and of low fertility status. The composite soil sample in 2015 contained more nutrients than the initial contents except ECEC. The increments were: organic carbon (0.09 g/kg), total N (0.03 g/kg), and available P (0.10 mg/kg), while exchangeable Ca, Mg and K increased by 0.10, 0.10 and 0.02 cmol/kg respectively whereas ECEC was depleted by 1.25 cmol/kg. The results also indicated enhanced performance of treated plants in both cropping seasons. Significantly (P = .05) tallest plants which also produced the highest number of branches with thickest stems, largest leaves and highest leaf yield were obtained in plots fertilized with the highest cowdung manure rate (9.0t/ha) in both seasons. At this level of cowdung application, plant height, stem girth and leaf yield were 76.3 cm, 3.6 cm and 27.2 t/ha, respectively in 2014, while in 2015, the corresponding values were 76.3 cm, 3.5 cm and 27.6 t/ha. Conclusion: The best crop response obtained at the highest cowdung manure rate could be an indication that higher yield is still possible at rates higher than 9.0 t/ha.